2005
DOI: 10.1002/jmv.20415
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of HCV infection in French hemodialysis units: A prospective study

Abstract: A large prospective study was carried out from 1997 to 2000 in 25 French hemodialysis units including 1,323 patients to determine the incidence of hepatitis C virus (HCV) infection. Monthly testing of alanine aminotransferase (ALT) activity, and assessment of HCV RNA and anti-HCV antibodies if the ALT activity was elevated, identified 14 new infections in 7 different units, giving an incidence of 0.4% new HCV infections per year. Molecular analyses and epidemiological data indicated that five patients became i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 46 publications
(53 reference statements)
1
48
1
1
Order By: Relevance
“…per 100,000 person-years (5), but lower than European and Japanese rates reported in hemodialysis populations (0.4 per 100 person-years to 2.59 per 100 person-years) (27)(28)(29). We found that younger age, history of transplant and history of past HBV infection were associated with HCV infection (19,30,31).…”
Section: Figure 1) Flow Chart Of Hepatitis C Virus (Hcv) Test Resultsmentioning
confidence: 61%
“…per 100,000 person-years (5), but lower than European and Japanese rates reported in hemodialysis populations (0.4 per 100 person-years to 2.59 per 100 person-years) (27)(28)(29). We found that younger age, history of transplant and history of past HBV infection were associated with HCV infection (19,30,31).…”
Section: Figure 1) Flow Chart Of Hepatitis C Virus (Hcv) Test Resultsmentioning
confidence: 61%
“…Hepatitis B and C in hemodialysis patients in Lebanon as low as 0.4% was observed in France from 1997 to 2000 [20] but higher rates have been reported from the Mediterranean region. According to the 2008 SCOT report, the annual rate of HCV sero-conversion in Saudi HD patients was 7%-9% while in Jordan it was 2.6% [14] .…”
Section: Discussionmentioning
confidence: 92%
“…25 The aminotransferase level might be slightly elevated and transitory. 1 This has a practical signifi cance since for all cases in which there is unexplained ALT increase, even a very slight increase, acute HCV infection should be suspected. It is only by monthly ALT testing of non-infected patients that an ALT increase could be detected.…”
Section: Resultsmentioning
confidence: 99%
“…At present, the main mode of HCV infection transmission is nosocomial. 1 HCV prevalence varies considerably for the different hemodialysis centres throughout the world -it is very low in the developed countries, especially in Germany (6.1%) and the United Kingdom (3.9%), but it is substantially high in the Middle East countries (Kuwait 71%). [2][3][4] HCV infection in dialysis patients tends to run an asymptomatic course with mild changes in the laboratory and morphology parameters.…”
Section: Introductionmentioning
confidence: 99%